UJI KEEFEKTIFAN EKSTRAK ALELOPATI AKAR TEKI (Cyperus rotundus L.) DAN BANDOTAN (Ageratum conyzoides L.) TERHADAP PERTUMBUHAN SAWI HIJAU (Brassica rapa L.) - Sri Rahayu; Asri Pirade Paserang; Wahyu Harso (Biocelebes, 2020)
Weeds such as Cyperus rotundus L. dan Ageratum conyzoides L. release allelopatic compounds which can inhibit the growth of crops. The aim of this study was to compare the inhibition of allelopatic compounds contained C. rotundus L. and A. conyzoides root exctract to Brassica rapa L. growth. This study was conducted in a greenhouse and was based on Completely Randomized Design with two factors. The first factor was type of root extracts (extract from either C. rotundus root or A. conyzoides root) and the second factor was concentration of root extract. Root extract concentrations added to growth medium of B. rapa L. 10 days after planting were 0, 100, 300 and 500 g/L respectifely. The addition of root extract was repeated every week until crop harvested. The results showed that there was not significantly different between C. rotundus and A. conyzoides roots extract to inhibit B. rapa growth. Increassing of root extract concentrations from both roots increased inhibition of B. rapa growth.